PIJAT REFLEKSI TENGKUK TERHADAP PENURUNAN TEKANAN DARAH PADA PASIEN HIPERTENSI DI RUMAH SAKIT GRANDMED LUBUK PAKAM - Abdi Lestari Sitepu; Pratiwi Christa Simarmata; Sari Desi Esta Ulina Sitepu; Amelia Sarma; Elfrida Simanjuntak (JURNAL KEPERAWATAN DAN FISIOTERAPI (JKF), 2021)
Hypertension is one of the deadliest diseases in the world, hypertension is an increase in systolic blood pressure above the normal limit of more than 140 mmHg and diastolic blood pressure of more than 90 mmHg, factors that cause increased blood pressure are physical activity, emotion, age, gender , nutritional status, drinking alcohol, smoking, stress. Data from the Grandmed Lubuk Pakam Hospital in 2018 the number of hypertension patients there were 178 cases of hypertension, the number of men was 82 people and women 96 people. One of the non-pharmacological therapies offered to reduce hypertension is massage therapy. The massage technique can remove blockages in the blood vessels so that blood and energy flow in the body returns smoothly. This research was conducted using a quasi-experimental design with the type of design to be used, namely the static group comparison method, the sampling technique used was non-probability sampling with purposive sampling technique, where the sample of this study was 20 people. The results showed that the pre-test sample in the treatment group was known to have the highest value of 160/100 mmHg and the lowest value of 130/90 and post-test mmHg with an average pre-test blood pressure value of 142.00 on systolic and 93.00 on diastolic, and 110.00 post-test. in systole and 79.00 in diastole. Based on the results above, it can be concluded that there is a relationship between reflexology neck massage with a decrease in blood pressure in patients with hypertension where the Wilcoxon Test results obtained p = 0.004 (systolic blood pressure) and p = 0.005 (diastolic blood pressure).